Web-Based Data Integration and Interoperability for a Massive Spatial-Temporal Dataset of the Heihe River Basin EScience Framework. (5th October 2015) - Guo, Qingchun; Zhang, Yaonan; He, Zhenfang; Min, Yufang
Abstract : To solve the messy problem of data types and form a unified data-processing solution, data in the Heihe River Basin were first classified into five types to integrate them and achieve unified management of data and metadata, preventing the loss of metadata, in the data model of eScience framework. Considering many of the challenges that exist in the construction of the online spatial-temporal data integration and interoperability eScience platform, we used the open data interfaces and standards such as the Common DataModel (CDM) interface, common scientific data modelling (i.e., NetCDF, GRIB, and HDF), and Open Geospatial Consortium (OGC) standards. Through the eScience platform, we also provided online data processing tools by collecting free tools (e.g., NetCDF tool, quality control tool). This eScience platform enables researchers to make full use of scientific research information and results and facilitates collaboration, especially between the GIS community and other members of the earth science community, with the purpose of establishing an online platform of uniform spatial data from the Heihe River Basin via common scientific data modelling.